Mechanisms of Er Chen Tang on Treating Asthma Explored by Network Pharmacology and Experimental Verification - Ren, Yuzhe; Zhang, Haijing; Yu, Zhou; Yang, Xiangzheng; Jiang, Deyou (Combinatorial Chemistry & High Throughput Screening, 2024)
Objective: The aim of this study is to explore the active ingredients of ECT and their targets for asthma and investigate the potential mechanism of ECT on asthma. Methods: Firstly, the active ingredients and target of ECT were screened for BATMAN and TCMSP, and functional analysis was done via DAVID. Then, the animal model was induced by ovalbumin (OVA) and aluminum hydroxide. Eosinophil (EOS) counts, EOS active substance Eosinophilic cationic protein (ECP) and eotaxin levels were detected following the instruction. Pathological changes in lung tissue were examined by H staining and transmission electron microscopy. Interleukin (IL-4, IL-10, IL-13, TNF-α), TIgE and IgE levels in bronchoalveolar lavage fluid (BALF) were measured by ELISA. Finally, the protein expression of the TGF-β / STAT3 pathway to lung tissue was detected by Western Blot. Results: A total of 450 compounds and 526 target genes were retrieved in Er Chen Tang. Functional analysis indicated that its treatment of asthma was associated with inflammatory factors and fibrosis. In the animal experiment, the results showed that ECT significantly regulated inflammatory cytokine (IL-4, IL-10, IL-13, TNF-α) levels in (P <0.05, P<0.01, reduced EOS number (P <0.05) and also ECP and Eotaxin levels in the blood (P <0.05) in BALF and/or plasma. Bronchial tissue injury was obviously improved on ECT treatment. Associated proteins in TGF-β / STAT3 pathway were significantly regulated by ECT (P <0.05). Conclusion: This study originally provided evidence that the Er Chen Tang was effective in the treatment of asthma symptoms, and its underlying mechanism might be the regulation of inflammatory factor secretion and the TGF-β/STAT3 signaling pathway.
Keywords: pharmacology network